Hereditary Increase of Plasma Histidine-Rich Glycoprotein Associated with Abnormal Heparin Binding (HRG Eindhoven) - Hoffmann, J J M L; Hennis, B C; Kluft, C; Vijgen, M (Thrombosis and Haemostasis, 1993)
Plasma histidine-rich glycoprotein (HRG) was found to be persistently increased in a patient with a history of recurrent arterial thromboembolic events. The mean concentration was 270% of normal pooled plasma. Increased HRG was found in eight of the 17 relatives studied, but none of them has experienced thrombo-embolism yet. Apparently, increased HRG was hereditary with autosomal dominant inheritance. A significant correlation was found between the increased plasma concentration of the protein and the age of the subjects (P<0.02), whereas no such relation is present in a normal population.The plasma HRG of the proposita and 9 of her family members displayed abnormal binding to heparin, as assessed in a crossed affinity immuno-electrophoresis system: the usual increase in mobility after binding to heparin was absent. The binding of this variant HRG to plasminogen was normal. This case represents the first abnormal HRG variant reported and it is proposed to designate it: HRG Eindhoven.